The Determinants of Political Discussion: How Important are Audit Courts and Local Autonomy? - Benno Torgler; Christoph A. Schaltegger (Center for Research in Economics, Management and the Arts (CREMA), 2005)
The intention of this paper is to analyse how audit courts and local autonomy affect political discussion, controlling in a multivariate analysis for a broad variety of potential factors focusing on Switzerland, due to its variety of audit court competences and its strong decentralised structure. With data from the World Values Survey 1995-1997 (Swiss data 1996) evidence has been found that a higher audit court competence and a lower level of centralization is correlated with a higher level of political discussion. Thus, the results in Switzerland suggest that such institutions help improve citizens' willingness to acquire information costs and discuss political matters.
Keywords: D72; H41; 330; Political Discussion; Institutions; Audit Courts; Local Autonomy; Decentralisation; Switzerland